2013
DOI: 10.1111/hiv.12064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two HIV testing strategies in primary care centres: indicator‐condition‐guided testing vs. testing of those with non‐indicator conditions

Abstract: , patients aged from 18 to 65 years old who attended a PCC for a new herpes zoster infection, seborrhoeic eczema, mononucleosis syndrome or leucopenia/ thrombopenia were included in the IC group, and one in every 10 randomly selected patients consulting for other reasons were included in the NIC group. A proportion of patients in each group were offered an HIV test; those who agreed to be tested were given a rapid finger-stick HIV test (€6 per test). Epidemiological and clinical data were collected and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
2
18
1
1
Order By: Relevance
“…Novel HIV testing technologies were employed by 40 studies in a wide range of clinical settings to increase testing coverage; the majority utilized rapid testing (n = 36) [18,19,22,24,25,34,36,45,46,[48][49][50]56,57,59,65,75,77,81,83,85,88,89,[99][100][101]107,113,117,129,132,134,137,139,141] while four utilized self-sampling (n = 3) [44,52,102] and self-testing strategies (n = 1) [108]. Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample.…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel HIV testing technologies were employed by 40 studies in a wide range of clinical settings to increase testing coverage; the majority utilized rapid testing (n = 36) [18,19,22,24,25,34,36,45,46,[48][49][50]56,57,59,65,75,77,81,83,85,88,89,[99][100][101]107,113,117,129,132,134,137,139,141] while four utilized self-sampling (n = 3) [44,52,102] and self-testing strategies (n = 1) [108]. Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample.…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
“…Routine testing was most commonly implemented in hospital departments including emergency departments (n = 15) [20,21,25,35,36,64,69,78,92,93,[115][116][117]137,147], inpatient units (n = 10) [24,43,61,95,98,104,111,125,130,135] and outpatient departments (n = 4) [21,74,113,116]. Similarly, IC testing programmes were predominantly instigated in hospitals (n = 8) [109,114,116,[125][126][127][128]135] and primary care (n = 10) [26,38,47,57,88,110,114,116,127,128]. In contrast, integrated testing for HIV with other infections such as hepatitis B and C and STIs was adopted in diverse settings including prisons (n = 3)…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
“…Data from the HIDES II audit in patients accessing care for a number of HIV ICs highlighted that testing rates in those with ICs remained low across Europe [23] with poor adherence to European guidelines recommending routine testing [21]. High HIV positivity rates were observed in individuals with AIDS defining and non-AIDS defining ICs within the HIDES study [23] and have also been reported in other studies [24]. Therefore, interventions are needed that prompt HCPs to offer a test when patients present with HIV ICs.…”
Section: Introductionmentioning
confidence: 64%
“…Two studies used more targeted approaches to HIV testing using preselected ICs [24,63]. Elias and colleagues developed an HIV risk exposure and ICs questionnaire using 14 preselected ICs to support targeted screening.…”
Section: Reference and Study Locationmentioning
confidence: 99%
“…Our group compared the direct cost of diagnosis of a previously unknown HIV infection in screening of the general population and screening guided by four ICs, and found the cost was €2001 and €129, respectively 8. These studies led to national and international recommendations to encourage IC-guided HIV test requests in PHC, based on the prevalence of HIV in these pathologies, their cost-effectiveness and healthcare sustainability 3 8.…”
Section: Introductionmentioning
confidence: 99%